Lithofacies analysis of the Catfish Creek till: Bradtville, Ontario - Huntley, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
Sedimentologic and facies analyses are used to interpret a section of Catfish Creek till at Bradtville, Ontario. Repetitive passive lodgement of debris-rich ice and gradual melt-out beneath active ice produced four massive matrix-supported diamicts (Dmm) separated by sand (Sg) and gravel (Gm) horizons. This sequence was partly reworked by melt-water focused along sand horizons, depositing cross-cutting Dcm, Sg and Gm facies. Post-depositional faulting also occurred. Deposition and glaciofluvial reworking are inferred to have occurred at some distance behind an alternately floated and grounded margin of the late Wisconsinan Erie Lobe.